MANAJEMEN MUTU TERPADU DI PESANTREN - Siti Aimah (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2021)
The purpose of this study is to find; planning, implementation, evaluation, follow-up, characteristics and impacts of quality standards on the application of integrated quality management in Pondok Pesantren Darussalam Blokagung and Pondok Pesantren Modern Al-Kautsar Banyuwangi. This study uses a qualitative approach to the data collection techniques used that are: observation, interviews and documentation. The data analysis technique uses interactive three models that are: data reduction, data presentation, conclusion drawing. The results of this research: first, the pattern of MMT application in pesantren is influenced by the typology of the education system used, but substantially has the same pattern of organizing, planning, implementing, monitoring and innovation. The pattern formed a cycle that repeated itself in the implementation of quality activities with the control of the person responsible for quality in collaboration with all stakeholders in the Islamic boarding school, especially the organizers of the managed educational activities; second, characteristics of MMT in pesantren that is focus on customers in providing satisfaction, total stakeholder involvement both internal and external in organizing quality activities, quality standards that are in line with customer desires, commitment of pesantren education service providers in supporting the improvement of quality culture, continuous improvement through improving quality standards in line with increasing customer expectations and innovation values ​​of the quality of the pesantren so that the public is increasingly in demand, prospective students and users, the integration of education and dual graduation is now increasingly in demand by the community; third the impact of implementing integrated quality management in pesantren is improvement of quality culture that triggers public appeal, to register their children in Islamic boarding schools and increasing number of students in pesantren, the increasing recognition of the quality (education) of pesantren in the community.